Evaluación de la sustentabilidad de las zonas productoras de tuna opuntia ficusíndica ( l. ) Mill.de la parroquia Eloy Alfaro, provincia de Cotopaxi. - Aguaisa Vivanco, Luis Patricio (2021)
The sustainability evaluation of agroecosystems through the use of indicators allows us to detect aspects of complex systems to transform them into clear objectives, guaranteeing the quality of life of the producers. The present research work was carried out in the prickly pear producing areas: Tanialo, Brazales and Santosamana from the Eloy Alfaro parish, Cotopaxi province. The objectives of this research were: to identify, characterize, evaluate and compare the prickly pear production systems through the use of Economic, Environmental and Socio-cultural sustainability indicators, for which a survey of 40 questions was applied to 16 producers of the locality, which were weighted according to their importance applying by Santiago Sarandón methodology, being able to determine that the Economic Indicator (IK) has a value of 2.42, the Environmental Indicator (IE) has a value of 1.27 and the Indicator Socio-cultural (ISC) has a value of 1.90, giving a General Sustainability Index of 1.86, concluding that it is not sustainable, having to adopt urgent changes in the three dimensions to improve sustainability with plans and actions that come from the actors and communities themselves. In order to identify the main phytosanitary problems, an interview was applied, obtaining as a result that the diseases that most affect the crop are: Anthracnose Colletotrichum sp., Alternaria sp. and Capnodium sp. that produces the "silver spot", while the pests that most affect the crop are: el Barrenador Laetilia coccidivora, el chinche gris Leptoglossus zonatus.